Designing and Manufacturing of Real Embedded Multi-Core CPUs: A Holistic Teaching Approach in Computer Architecture - Reichenbach, Marc; Pfundt, Benjamin; Fey, Dietmar (Proceedings of the Tenth Workshop on Microelectronics Education, 2014)
How to teach students current computer architecture? This is an important question in our modern world, where the market of embedded parallel processors is continuously growing. In every compact device today, such as smart phones and tablets, small and powerful multi-core architectures are present. Therefore, there is the need to teach students the whole range of embedded design - starting from the basics of computer architecture through to real chip design. In this paper, we present our experience with a holistic teaching approach in embedded multi-core computing, which covers most aspects of embedded system design. Beginning with the theoretical foundations of computer architecture, a custom multi-core CPU is designed by teams of students and finally transferred to a complete IC layout. As a distinctive feature, the layout is manufactured and packaged. The students will get their own processor chip, which they can test and evaluate. Student surveys show that the students are highly motivated to obtain the opportunity to produce their own chip. This results in active participation in the lessons/seminars and the training of valuable social skills. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD3.design
Keywords: CPU design; embedded computing education; IC design; multi-core; teaching computer architecture